FRI0661 Ultrasound of subtalar joint synovitis in patients with rheumatoid arthritis: results of an omeract reliability exercise using consensual definitions. (12th June 2018) - Bruyn, G. A.; Siddle, H.; Hanova, P.; Costantino, F.; iagnocco, A.; Delle Sedie, A.; Gutierrez, M.; Hammer, H.; Jernberg, E.; Loeille, D.; Micu, M.; Moller, I.; et al.
Abstract : Background: The incidence of subtalar joint (STJ) disease in patients with rheumatoid arthritis (RA) is greatly increased between five and ten years of disease duration and regularly precedes changes in the tibiotalar joint [1]. The joint is notoriously difficult to assess clinically and frequently overlooked in favour of the more accessible tibiotalar joint. We hypothesized that US might be used as a reliable outcome measure to evaluate synovitis of the STJ in patients with RA. The objectives of this study were first, to develop an expert consensus derived definition of synovitis and scanning protocol for the STJ and second, to test the reliability of the definitions and protocol. Objectives: To evaluate the intra- and interobserver reliability of the US assessment of STJ synovitis in patients with RA. Methods: Following a Delphi process, twelve sonographers conducted an US reliability exercise on 10 RA patients with hindfoot pain. The anteromedial, posteromedial, and posterolateral STJ was assessed using B-mode and power Doppler (PD) techniques according to an agreed US protocol and using a 4-grade semiquantitative grading score for synovitis (synovial hypertrophy (SH) and power Doppler (PD) signal) and a dichotomous score for the presence of joint effusion (JE). Intraobserver and interobserver reliability were computed by Cohen and Light kappa (k). Weighted k coefficients with absolute weighting were computed for B-mode and PD signal. Results: Mean weighted Cohen's kappa for SH, PD, and JE, was 0.80 (0.62–0.98), 0.61 (0.48–0.73), and 0.52 (0.36–0.67), respectively. Weighted Cohen's kappa for SH, PD, and JE in the anteromedial, posteromedial and posterolateral STJ was -0.04–0.79, 0.42–0.95, and 0.28–0.77; 0.31–1, -0.05–0.65, and -0.2–0.69; 0.66–1, 0.52–1, and 0.42–0.88, respectively. Weigthed Light kappa for SH was 0.67 (95%CI 0.58–0.74), 0.46 (0.35–0.59) for PD, and 0.16 (0.08–0.27) for JE. Weighted Light kappa for SH, PD, and JE was 0.63 (0.45–0.82), 0.33 (0.19–0.42) and 0.09 (-0.01–0.19), for the anteromedial; 0.49 (0.27–0.64), 0.35 (0.27–0.4), and 0.04 (-0.06–0.1) for posteromedial, and 0.82 (0.75–0.89), 0.66 (0.56–0.8), and 0.18 (0.04–0.34) for posterolateral STJ, respectively. Conclusions: Ultrasound is a feasible and reliable tool for assessing synovitis of the posterolateral STJ in RA, but not for the anteromedial and posteromedial STJ. SH can be reliably detected in B-mode and PD mode, but this is not true for JE. Reference: 1. Van der Leeden M, Steultjens MP, Van Ursem J, et al. Prevalence and course of forefoot impairments and walking disability in the first eight years of rheumatoid arthritis. Arthritis Rheum2008;59:1596–1602. Disclosure of Interest: None declared